Association of Left Atrial Appendage Morphology and Function with Stroke and Transient Ischemic Attack in Atrial Fibrillation Patients - Simon, Judit (Elsevier, 2025)
We aimed to correlate left atrial appendage (LAA) structure and function with the history of stroke/transient ischemic attack (TIA) in patients with atrial fibrillation (AF). We analyzed data of 649 patients with AF who were scheduled for catheter ablation. Patients underwent cardiac CT and transesophageal echocardiography prior to ablation. LAA morphologies depicted by cardiac CT were categorized into four groups: cauliflower, chicken wing, swan and windsock shapes. Mean age was 61.3±10.5 years, 33.9% were female. Prevalence of stroke/TIA was 7.1%. After adjustment for the main risk factors, LAA flow velocity ≤35.3 cm/sec (OR=2.18; 95%CI=1.09-4.61; p=0.033) and swan LAA shape (OR=2.69; 95%CI=0.96-6.86; p=0.047) independently associated with higher risk of stroke/TIA, while windsock LAA morphology proved to be protective (OR=0.32; 95%CI=0.12-0.77; p=0.017) as compared to cauliflower LAA shape. When comparing the differences between LAA morphology groups, we measured significantly smaller LAA orifice area (389.3±137.7 mm2 in windsock vs 428.3±158.9 ml in cauliflower, p=0.021) and LAA volume (7.4±3.0 mm2 in windsock vs 8.5±4.8 mm2 in cauliflower, p=0.012) in patients with windsock LAA morphology, while LAA flow velocity did not differ significantly. Reduced LAA function and swan LAA morphology were independently associated with higher prevalence of stroke/TIA, while windsock LAA shape proved to be protective. When comparing the differences between the various LAA morphology types, significantly lower LAA volume and LAA orifice area were measured in windsock LAA shape as compared to cauliflower LAA shape.